"Dzienniki" Marii Dąbrowskiej jako sztuka życia, życie jako dzieło sztuki - Kałowska, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
Diaries of Maria Dąbrowska have been written during all author’s adult life, since the year 1914 till 1965. They are one of the greatest Polish examples of literary genre which was born in France and called journal intime. The aim of this article to propose a new way of reading it: as expression of art of living, as an aesthetisation of every day life, using categories created by Richard Shusterman in his book Practising philosophy. Pragmatism and philosophical life, which was inspired by John Dewey’s Art as experience.